Position Permission Divorce for Civil Servants at the Class 1A Religious Court Office in Makassar - Baharuddin, Muhammad Fadil; Nawi, Syahruddin; Pusvita Aziza, Dian Eka (Faculty of Law, Universitas Muslim Indonesia, 2025)
Study This aiming For know and understand mechanism submission permission for Civil servants who carry out divorce at the Class 1A Religious Court Office in Makassar. And for know and understand factor affecting​ submission permission for Civil servants who carry out divorce at the Class 1A Religious Court Office in Makassar. Research This use method study empirical that is a approach or method knowledge based​ observation direct , observation , and observation . Research results This show Civil servants who want to submit application permission divorce must with legitimate reasons​ to official authorized Then official authorized to form team advisory after That call second split party husband wife simultaneously or individually . Officials give advice to be able to harmony Back but if second split party or one of them party want to divorce so both of them must make statement want to divorce . The factors that influence submission permission divorce that is factor internal and external factors external . Recommendations given​ writer that is Firstly, civil servants at the Class 1A Religious Court in Makassar must own permission If want to carry out divorce . The second one give certainty law and sense of justice in take or emit permit decision letter divorce for civil servants.